2015
DOI: 10.1111/imm.12503
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathogenic RBP‐3 peptide reveals epitope spreading in persistent experimental autoimmune uveoretinitis

Abstract: SummaryExperimental autoimmune uveoretinitis (EAU) in the C57BL/6J mouse is a model of non-infectious posterior segment intraocular inflammation that parallels clinical features of the human disease. The purpose of this study was to analyse the immune response to the four murine subunits of retinol binding protein-3 (RBP-3) to identify pathogenic epitopes to investigate the presence of intramolecular epitope spreading during the persistent inflammation phase observed in this model of EAU. Recombinant murine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The study of EAU have shown that it is important to use human protein sequences in epitope mapping for human immune responses because the amino acid differences between experimental animals and human sequences may affect the identification of novel pathogenic epitopes and the determination of epitope spreading. In the EAU model, epitope spreading from the immunizing to the non-immunizing peptide was demonstrated for both IRBP 1–20 and 629–643 sequences and was consistent with the destruction of retinal tissue, increasing repertoire of antigen-specific effector T-cell with disease progression ( 102 ).…”
Section: Importance Of Epitope Mapping In Armentioning
confidence: 92%
“…The study of EAU have shown that it is important to use human protein sequences in epitope mapping for human immune responses because the amino acid differences between experimental animals and human sequences may affect the identification of novel pathogenic epitopes and the determination of epitope spreading. In the EAU model, epitope spreading from the immunizing to the non-immunizing peptide was demonstrated for both IRBP 1–20 and 629–643 sequences and was consistent with the destruction of retinal tissue, increasing repertoire of antigen-specific effector T-cell with disease progression ( 102 ).…”
Section: Importance Of Epitope Mapping In Armentioning
confidence: 92%
“…From a practical perspective, future work could focus on validating theoretical results presented in this paper using experimental measurements of the progress of autoimmune disease in animal hosts, with experimental autoimmune uveoretinitis (EAU), an autoimmune inflammation in the eyes, being one interesting possibility. In one such recent experiment, all animals were genetically identical C57BL/6 mice, but once the EAU was induced in them through inoculation, the autoimmune disease then progressed at slightly different rates [77], (Boldison and Nicholson, 2012) and the measured variability in the numbers of infected cells and T cell responses could be compared to theoretical estimates of the variance as predicted by our model. From a clinical perspective, comparison of variance in the measured populations of different cells with the model conclusions will facilitate an efficient parameter identification and provide a set of prognostic criteria for the progress of autoimmunity, which can be used for risk stratification and assessment of patients with autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated the importance of minimally activated CD8 + T cells in uveitis in rats and mice (16)(17)(18)(19), and CD8 + T cells are present in eyes of uveitis patients (20,21). While it is clear that effector CD8 + T cells are involved in the inflammatory immune response, the connection with activation of these cells with the melanocortin-adenosinergic pathway is paradoxical.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that CD8 + T cells have a role in uveitis through observations in rodent models of EAU (16)(17)(18)(19), and analysis of aqueous humor from uveitis patients (20,21). MC5r transcript expression has been reported in CD8 + T cells from human PBMCs (22) but protein expression was not confirmed and the role of MC5r in this cell subset has not been further examined.…”
Section: Introductionmentioning
confidence: 99%